Anterior cervical fusion with interbody cage containing beta-tricalcium phosphate: Clinical and radiological results - Ali Ender Ofluoglu; Uzay Erdogan; Mehmet Aydogan; Orhun Mete Cevik; Onder Ofluoglu (Acta Orthopaedica et Traumatologica Turcica, 2017)
Aim: Beta tricalcium phosphate (beta-TCP) is an osteoconductive, resorbable material. Its clinical effectiveness has been proved in many indications. This study was clinical and radiographic study report obtained in patients undergoing anterior cervical discectomy and fusion ACDF in which PEEK cages were filled beta-TCP in an injectable form. Material and methods: Between January 2010 and June 2011, 16 consecutive patients underwent ACDF using PEEK cages with beta-TCP. The cohort compromised 10 men and 6 women with a mean age of 45.2 years. The surgery was performed when the patient had myelopathy or radiculopathy with progressive neurological deficit, or failure of conservative treatment (a minimum of 3 months). The patients were evaluated by Odom criteria preoperatively and postoperative 3rd, 6th, 12th and 24th months. Preop and postop pain was evaluated with visual analogue scala (VAS). Disc height and fusion success rates were evaluated. Results: Preoperative average VAS score was 7.9 (7–10) for neck pain and 8 (7–10) for arm pain. At the final follow-up, these scores became 1.5 and 1.4 for neck and arm pain, respectively. The average improvement rate was 81% for neck pain and 82.5% for arm pain. Postop ODOM's criteria main rate was 3.4. Bone fusion was achieved in 14 segments (70%) at 3rd month, 19 segments (95%) at 12th month follow-up assessment. Conclusion: Clinical and radiological results revealed that B-TCP is a good alternative synthetic fusion material for cervical interbody fusion.Level of evidence: Level IV, therapeutic study. Keywords: Anterior cervical fusion, Interbody cage, Beta-tricalcium phosphate